2003
DOI: 10.1177/229255030301100207
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Basal Cell Carcinoma: A Case Report

Abstract: An unusual case of a patient who presented with a subcutaneous soft tissue lesion of the back is described. The patient had no preceding history of cutaneous malignancy or local trauma. Excision of the lesion revealed a diagnosis consistent with basal cell carcinoma with deep infiltration. The site was re-excised with a generous margin to ensure complete removal. There has been no recurrence for 18 months. This case is presented to underscore the rarity and importance of its existence.Key Words: Basal cell can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…1 In 2003, Tenley Vouris et al reported a 21-year-old white woman who presented with a 6-month history of a slowgrowing, subcutaneous lesion, described as measuring 1.2 9 1.2 cm on her mid upper back. 2 Salih et al described a 40-year-old male Kurdish driver, who presented with a tender, mobile, round, soft mass, with a reported measurement of 4 9 2.5 cm, on the sacrococcygeal area just to the right of the midline. 3 Our case highlights that in addition to common causes such as lipoma and epidermoid cyst, rarer conditions such as subcutaneous BCC need to be considered in the differential diagnosis of a subcutaneous soft tissue mass.…”
mentioning
confidence: 99%
“…1 In 2003, Tenley Vouris et al reported a 21-year-old white woman who presented with a 6-month history of a slowgrowing, subcutaneous lesion, described as measuring 1.2 9 1.2 cm on her mid upper back. 2 Salih et al described a 40-year-old male Kurdish driver, who presented with a tender, mobile, round, soft mass, with a reported measurement of 4 9 2.5 cm, on the sacrococcygeal area just to the right of the midline. 3 Our case highlights that in addition to common causes such as lipoma and epidermoid cyst, rarer conditions such as subcutaneous BCC need to be considered in the differential diagnosis of a subcutaneous soft tissue mass.…”
mentioning
confidence: 99%